Arbuscular Mycorrhizal Association of Populus deltoides - Uniyal, Kamla (Indian Forester, 2003)
Arbuscular mycorrhizal association was studied in Populus deltoides plantation in New Forest, Dehra Dun (Uttaranchal) during the year 1994 from Jan-Dec. The frequency of AM fungi varied during different months. Five mycorrhizal genera viz., 3 species of Acaulospora, 10 species of Glomus, 3 species of Scutellospora, 3 species of Sclerocystis and 2 species of Gigaspora were found associated with P. deltaides.